A sensitive assay for trypsin using poly(thymine)-templated copper nanoparticles as fluorescent probes. Issue 6 (21st March 2015) - Ou, Li-Juan; Li, Xiao-Yan; Li, Li-Juan; Liu, Hong-Wei; Sun, Ai-Ming; Liu, Kai-Jian
<x xml:space="preserve">Abstract</x> A novel fluorescence assay for trypsin was developed based on trypsin-catalyzed hydrolysis of cytochrome c-induced fluorescence quenching of CuNPs.